CHANGES TO SATURN'S ZONAL-MEAN TROPOSPHERIC THERMAL STRUCTURE AFTER THE 2010-2011 NORTHERN HEMISPHERE STORM - Achterberg, R; Gierasch, P; Conrath, B; Fletcher, L; Hesman, B; Bjoraker, G; Flasar, F (Institute of Physics Publishing, 2014)
We use far-infrared (20-200 μm) data from the Composite Infrared Spectrometer on the Cassini spacecraft to determine the zonal-mean temperature and hydrogen para-fraction in Saturn's upper troposphere from observations taken before and after the large northern hemisphere storm in 2010-2011. During the storm, zonal mean temperatures in the latitude band between approximately 25°N and 45°N (planetographic latitude) increased by about 3 K, while the zonal mean hydrogen para-fraction decreased by about 0.04 over the same latitudes, at pressures greater than about 300 mbar. These changes occurred over the same latitude range as the disturbed cloud band seen in visible images. The observations are consistent with low para-fraction gas being brought up from the level of the water cloud by the strong convective plume associated with the storm, while being heated by condensation of water vapor, and then advected zonally by the winds near the plume tops in the upper troposphere. © 2014. The American Astronomical Society. All rights reserved.